2009
DOI: 10.1007/s11250-009-9489-2
|View full text |Cite
|
Sign up to set email alerts
|

A study on superovulation using FSH and eCG in Awassi ewes

Abstract: The present study was conducted to evaluate superovulatory treatments in Awassi ewes by eCG and FSH. High number of unovulated follicles (P < 0.05) was observed in ewes treated with eCG in non-breeding season. It could be concluded that using FSH to induce superovulation in Awassi ewes is better than eCG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…However, the latest research was conducted in the breeding season, but we challenged the feeding out of breeding season and anestrous Qezel ewes. In this regard, previous studies confirmed higher ovarian responses during the breeding season than in the non-breeding season in different breeds of ewes [53][54][55]. The breeding season and the cyclicity would probably affect the response of the ovary and uterine environment or even the endocrine system related to reproduction upon incorporating the diet with LO or probably other FAs.…”
Section: Discussionmentioning
confidence: 82%
“…However, the latest research was conducted in the breeding season, but we challenged the feeding out of breeding season and anestrous Qezel ewes. In this regard, previous studies confirmed higher ovarian responses during the breeding season than in the non-breeding season in different breeds of ewes [53][54][55]. The breeding season and the cyclicity would probably affect the response of the ovary and uterine environment or even the endocrine system related to reproduction upon incorporating the diet with LO or probably other FAs.…”
Section: Discussionmentioning
confidence: 82%
“…The 400 IU dose of eCG favored the percentage of double births and the prolificacy index when modifying the ovulatory rate. A high dose of eCG in estrus induction and synchronization protocols causes a superovulatory effect in ewes and, therefore, an increase in prolificacy (Zeleke et al, 2005;Azawi and Al-Mola, 2010;Quintero-Elisea et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…A number of reports have shown FSH to be superior to eCG in terms of ovulation rate and embryo viability in sheep; for example, FSH produced more embryos than eCG in Suffolk ewes (5.3 vs. 3.5) [70], native Saloia sheep (5.8 and 3.6) [82], and Awassi ewes (4.83 vs. 4.66) [68] (Table 1). Moreover, few attempts have been made at comparing the multidose FSH protocol with the eCG plus FSH single injection (Table 1) [29,35].…”
Section: Gonadotrophins and Superovulationmentioning
confidence: 99%
“…Different gonadotropins exhibit varied superovulatory responses, a detailed discussion of which can be found in the introductory section of this review, and outlined in Table 1 . A number of reports have shown FSH to be superior to eCG in terms of ovulation rate and embryo viability in sheep; for example, FSH produced more embryos than eCG in Suffolk ewes (5.3 vs. 3.5) [ 70 ], native Saloia sheep (5.8 and 3.6) [ 82 ], and Awassi ewes (4.83 vs. 4.66) [ 68 ] ( Table 1 ).Moreover, few attempts have been made at comparing the multidose FSH protocol with the eCG plus FSH single injection ( Table 1 ) [ 29 , 35 ]. In sum, there are discrepancies in the outcomes regarding the use of FSH in combination with eCG, whether it produces a better superovulatory response than FSH alone, and whether this response is improved by multiple injections or a single injection of eCG.…”
Section: Factors Affecting Outcomes Of Superovulationmentioning
confidence: 99%
See 1 more Smart Citation